Performance-differences in speed profiles and tactical choices in a cross-country skiing mass-start competition - Wolf, H. (Norwegian University of Science and Technology, 2022)
The aim of the present study was to compare speed profiles and tactical choices between cross-country skiers on different performance levels in a mass-start cross-country skiing competition by describing the race development and individual speed profiles over the entire race and identifying differences in speed profiles and the tactical choices distinguishing skiers on different performance levels.